Postpartum Contraception: What Do Our Patients Understand? [10O]. (May 2016) - Paredes, Ingrid; Anasti, James; Stoltzfus, Jill
Abstract : INTRODUCTION: Early contraception use in the postpartum period (PP) has been shown to increase the interval to subsequent pregnancy. Efforts to increase patients understanding of types of contraception may improve their usage. METHODS: We developed a 15 minute contraceptive instructional video (English and Spanish) to be shown to our day 2 postpartum patients (PPD2). The video explains the various forms of contraception, including usage, efficacy, side effects and contraindications. Prior to the video PPD2 patients were given a simple 7 question survey to determine their understanding of PP contraception. They were then instructed to watch the video and to retake the quiz within 2 hours of watching the video. RESULTS: We gave the video to 60 PPD2 patients. The mean age was 22±3 yrs and mean parity of 1±0.5. Although not statistically significant, the pre and post survey results demonstrated trend to an increase understanding of some methods. Of particular interest was the failure of the video to increase individuals understanding of what is required to insert an IUD and PP oral contraception use (OCP). Pre-video survey revealed 23% thought one "… needed to go to OR for IUD insertion." This was unchanged after viewing video. Pre-video, 52% thought OCPs were safe to use immediately after delivery, this dropped to 45% post video. CONCLUSION: Information regarding IUD and PP OCP use may require additional, if not separate, educational counseling to better inform our patients about these PP contraceptive options.